Maurice Samuel : life and letters of a secular Jewish contrarian - Levenson, Alan T. (Jews and Judaism: history and culture, 2022)
"This short intellectual biography reassesses one of the premier Jewish humanists of the mid-twentieth century, the Rumanian-born, English-educated, American belletrist Maurice Samuel. Although he spoke in a staccato Midlands accent, Samuel left Manchester, England in 1913, joined the American Army, served in military intelligence in World War I, and became a United States citizen. Samuel resettled his family in Palestine in 1929, then returned to the US, and spent his most creative years in New York City. A diaspora intellectual, or "rootless cosmopolitan," as Alan Levenson describes him, Samuel made an indelible mark on many features of contemporary Jewish thought and culture"--